2014
DOI: 10.1016/j.watres.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalytical and chemical evaluation of disinfection by-products in swimming pool water

Abstract: Pool water disinfection is vital to prevent microbial pathogens. However, potentially hazardous disinfection by-products (DBP) are formed from the reaction between disinfectants and organic/inorganic precursors. The aim of this study was to evaluate the presence of DBPs in various swimming pool types in Brisbane, Australia, including outdoor, indoor and baby pools, and the dynamics after a complete water renewal. Chemical analysis of 36 regulated and commonly found DBPs and total adsorbable organic halogens as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 62 publications
10
82
0
Order By: Relevance
“…S1, the concentrations of these compounds detected in indoor pools (mean 144 ng L −1 ) were roughly 20-fold higher than those in outdoor pools (mean 6.78 ng L −1 ). This result is consistent with previous reports that concentrations of DBPs in indoor pools were higher than those in outdoor pools (Xiao et al 2012;Yeh et al 2014). Compared to the indoor pools, opening times for outdoor pools are usually short.…”
Section: Comparison Of Different Poolssupporting
confidence: 94%
“…S1, the concentrations of these compounds detected in indoor pools (mean 144 ng L −1 ) were roughly 20-fold higher than those in outdoor pools (mean 6.78 ng L −1 ). This result is consistent with previous reports that concentrations of DBPs in indoor pools were higher than those in outdoor pools (Xiao et al 2012;Yeh et al 2014). Compared to the indoor pools, opening times for outdoor pools are usually short.…”
Section: Comparison Of Different Poolssupporting
confidence: 94%
“…Conversely, Kanan [7] and Yeh et al [8] observed that the concentration of DCAA and TCAA was higher in EGMO disinfected pools compared with the chlorinated pools. For instance, the concentration of DCAA in chlorinated and EGMO disinfected indoor pools was 1233 µg·L −1 and 2400 µg·L −1 , respectively, and the concentration of TCAA in chlorinated and EGMO disinfected indoor pools was 1153 µg·L −1 and 2600 µg·L −1 , respectively [8] (Table A4).…”
Section: Effect On Haasmentioning
confidence: 92%
“…With this awareness, the demand for alternatives to chlorine disinfection has increased. The alternative methods aimed at improving the quality of swimming pool water are: electrochemically generated mixed oxidants (EGMO) [3,[5][6][7][8], ultraviolet (UV) irradiation [9][10][11][12], UV-based advanced oxidation processes (UV-based AOPs) such as UV/H 2 O 2 [13], ozone (O 3 ) [14][15][16], and ozone-based AOPs such as O 3 /H 2 O 2 and O 3 /UV [17][18][19]. The use of O 3 and UV irradiation for the disinfection of swimming pool water has been adopted in some cases, though together with chlorine for the provision of a residual disinfectant [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For bioassays, 500 mL of ozonated samples were also subjected to 24-h formation potential tests with chlorine. The residual chlorine was quenched with equimolar concentrations of sodium thiosulfate (Na 2 S 2 O 3 ·5H 2 O; 99.5%, Sigma-Aldrich, USA) (Farré et al 2013, Yeh et al 2014.…”
Section: Dbp Formation Potential Testsmentioning
confidence: 99%